Digital Compilation and Arrangement of the Religious Sports Heritage of the Yao Nationality In Hunan - Lei, Jian (Journal of Theory and Practice of Social Science, 2024)
On the basis of analyzing the status quo of yao nationality's sports heritage protection in Hunan, this paper discusses the significance of digital protection of religious sports heritage, and discusses the strategy of digital compilation and collation of Yao nationality's religious sports heritage. Resource survey and data collation are put forward. Intelligent platform and digital museum construction; Leisure entertainment and industrialization development; the four ways and measures of digital talent training provide theoretical reference and technical support for the protection and development of yao religious sports heritage in Hunan.